A European proficiency test on thin‐film tandem photovoltaic devices. (10th September 2020) - Salis, Elena; Gerber, Andreas; Andreasen, Jens Wenzel; Gevorgyan, Suren A.; Betts, Tom; Mihaylov, Blagovest; Gottschalg, Ralph; Kodolbaş, Alp Osman; Yilmaz, Okan; Leidl, Roman; Rennhofer, Marcus; Zamini, Shokufeh; et al.
Abstract: A round‐robin proficiency test (RR PT) on thin‐film multi‐junction (MJ) photovoltaic (PV) cells was run between 13 laboratories within the European project CHEETAH. Five encapsulated PV cells were circulated to participants for being tested at Standard Test Conditions (STC). Three cells were a‐Si/μc‐Si tandem PV devices, each of which had a different short‐circuit current ratio between the top junction and the bottom one; the remaining two cells were single‐junction PV devices made with material representative of the individual junctions in the MJ cells. The RR PT's main purpose was to assess the capability of the participating laboratories, in terms of employed facilities and procedures, to test MJ PV devices. Therefore, participants were requested to perform STC measurements of all cells according to their own procedure, which might not include external quantum efficiency measurements. The European Solar Test Installation (ESTI) of the Joint Research Centre (JRC) provided the reference calibrations against which the participants' results are compared. ESTI made also a verification of the cells performance at STC at the end of the RR PT, in order to allow a comparison between the initial stable state at which the cells were calibrated (just before circulation) and the one they had reached at the end of the RR PT. The overall results of the RR PT are here presented and discussed together with some aspects of MJ PV testing that emerged as not adequately applied or largely missing. Their full implementation is expected to improve the consistency of future results. Abstract : A round‐robin proficiency test for STC performance assessment of multi‐junction photovoltaic cells was run between 13 laboratories with different levels of expertise, plus the JRC ESTI as the reference laboratory. Most laboratories show large P max deviations from the reference. These can be linked to inaccurate spectral corrections, which can originate from the reference cell(s) used to adjust the solar simulator, from spectral irradiance measurement, from DUT EQE measurement (e.g., no bias voltage application) or from a combination of all these.